Infant Mental Health Home Visiting Mitigates Impact of Maternal Adverse Childhood Experiences on Toddler Language Competence: A Randomized Controlled Trial. Issue 4 (25th May 2022) - Riggs, Jessica L.; Rosenblum, Katherine L.; Muzik, Maria; Jester, Jennifer; Freeman, Sarah; Huth-Bocks, Alissa; Waddell, Rachel; Alfafara, Emily; Miller, Alison; Lawler, Jamie; Erickson, Nora; Weatherston, Debbie; et al.
ABSTRACT: Objective: The goal of this study was to test the impact of maternal adverse childhood experiences (ACEs) on subsequent child language competence; higher parental ACEs were expected to predict risk of toddler language delay. Participation in Infant Mental Health Home Visiting (IMH-HV) treatment, which aims to enhance responsive caregiving and improve child social-emotional development, was expected to mitigate this association. Methods: A randomized controlled trial (RCT) design was used. ACEs data were collected at baseline. Child language screening (using the Preschool Language Scales Screening Test) was conducted 12 months later by masters-level evaluators who were blind to treatment condition. Visits occurred in participants' homes. Participants were community-recruited and were randomized to treatment (psychotherapeutic IMH-HV) or control (treatment as usual). Data come from 62 families who participated in all waves of an RCT testing the efficacy of IMH-HV; mothers were eligible based on child age (<24 mo at enrollment) and endorsement of ≥2 sociodemographic eligibility criteria (economic disadvantage, depression, perceived parenting challenges, and/or high ACEs). Results: The age of mothers enrolled in this ranged from 19 to 44 years (M = 31.91; SD = 5.68); child age at baseline ranged from prenatal to 26 months (M = 12.06; SD = 6.62). The maternal ACE score predicted child language competence ( t (5, 55) = −3.27, p = 0.002). This effect was moderated by treatment ( t (6, 54) = 1.73, p = 0.04), indicating no association between maternal ACEs and child language for those randomized to IMH-HV. Conclusion: The results highlight that the effects of parent ACEs on early childhood outcomes may be buffered by participation in psychotherapeutic home visiting (trial registration: NCT03175796).